The interactions of composting and biochar and their implications for soil amendment and pollution remediation: a review. (18th August 2017) - Wu, Haipeng; Lai, Cui; Zeng, Guangming; Liang, Jie; Chen, Jin; Xu, Jijun; Dai, Juan; Li, Xiaodong; Liu, Junfeng; Chen, Ming; Lu, Lunhui; Hu, Liang; et al.
Abstract: Compost and biochar, used for the remediation of soil, are seen as attractive waste management options for the increasing volume of organic wastes being produced. This paper reviews the interaction of biochar and composting and its implication for soil amendment and pollution remediation. The interaction of biochar and composting affect each other's properties. Biochar could change the physico-chemical properties, microorganisms, degradation, humification and gas emission of composting, such as the increase of nutrients, cation exchange capacity (CEC), organic matter and microbial activities. The composting could also change the physico-chemical properties and facial functional groups of biochar, such as the improvement of nutrients, CEC, functional groups and organic matter. These changes would potentially improve the efficiency of the biochar and composting for soil amendment and pollution remediation. Based on the above review, this paper also discusses the future research required in this field.